An Acceleration of Cendana (Santalum album) Growth Using Addition of Essential Macro Nutrients n on Three Types of Soil - Eny Faridah; Haryono Supriyo; M Gunawan Wibisono; Kristinawati Kristinawati; Dwi Afiani; Dian Hartanti (Jurnal Ilmu Kehutanan)
Sandalwood is one of important alternatives to use for rehabilitation programs of critical land areas in Indonesia. Therefore, due to its slow growth which held up forest rehabilitation program, attempts to accelerate its growth rate are crucially necessary. Considering that problem, the study is aimed to formulate an approach to accelerate cendana’s growth through the application of essential macro nutrients needed by cendana grown in three types of soil in the form of biofertilizers such as biofosfo and biosulfo. In a specific way, the study aimed to analyze 1) the effect of soil types ((Grumusol (Vertisol), Mediteran (Alfisol) dan Regosol (Entisol)) on growth of sandalwood, 2) the effect of fertilizer types and dosages on growth of sandalwood, and 3) the effect of soil type, and fertilizer types and dosages on nutrient content of soil and plants’ leaves. The research was conducted in Lab. of Intensive Silviculture, Klebengan, the Faculty of Forestry GMU using cendana seedlings of 6 months old. Research was applied using Completely Randomized Design (CRD) with treatments of 3 soil types (Grumusol (Vertisol), Mediterran (Alfisol) and Regosol (Entisol)), 3 fertilizer types (biosulfo, biofosfo, and NPK), and 5 fertilizer dosages (0, 2.5, 5, 7.5 and 10 g) with 5 replications for each experiment unit. Parameters assessed were plant growth rate (height & diameter growth, root length), and nutrient level of soil media and plant leaves. The results showed that Mediterran soil positively affected all growth parameters (height, diameter, root length) followed by Regosol dan Grumusol, while application of different fertilizers and dosages did not give significant effects on all plant growth parameters. Mediteran soil contained the highest N and K followed by Regosol and Grumusol, while Regosol contained the highest available P followed by Mediteran and Grumusol. Interaction between Grumusol and biofosfo/biosulfo, which resulted in lowest growth of all parameters, contained the lowest soil P level, indicating the role of phosphate on plant growth. During the 3-month period, the application of biofosfo, biosulfo dan NPK at different dosages increased leaf P, S and N level with no clear trend.